International Higher Education and the “Neo-liberal Turn” - Scott, Peter (International Higher Education, 2016)
International higher education, once an aspect of the academy associated with ideals of solidarity and development, is now seen as the most market-oriented aspect. The main reason for this reversal is the so-called ‘neoliberal turn’. But the major trends associated with this turn - a new (and reduced) role for the State; globalization in its various guises and the rise of new communicative cultures as a result of advances in information technology - are likely to have multiple and even contradictory impacts on higher education.